Thalictrum callianthum (Ranunculaceae) is merged with T. diffusiflorum - Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2017)
Critical examination of herbarium specimens (including type material) indicates that Thalictrum callianthum (Ranunculaceae), described from Mainling, south-east Xizang (Tibet), China, is conspecific with T. diffusiflorum, a species described from Nyingchi closely contiguous to Mainling and fairly common in south-east Xizang. We therefore place the former in synonymy with the latter.